2012
DOI: 10.1590/s0034-72802012000200005
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do conhecimento sobre urgências oftalmológicas dos acadêmicos da Faculdade de Medicina da Pontifícia Universidade Católica de Campinas

Abstract: RESUMOObjetivo: Avaliar os conhecimentos sobre urgências oftalmológicas (UO) dos acadêmicos da Faculdade de Medicina da Pontifícia Universidade Católica de Campinas (PUC-Campinas). Métodos: Estudo transversal (inqué-rito) realizado entre os acadêmicos do primeiro ano e último ano da graduação. Foi aplicado um questionário padronizado contendo uma autoavaliação na qual os acadêmicos graduaram seu conhecimento em "bom", "regular" ou "insuficiente" e 10 questões de múltipla escolha abordando temas de UO. Os dados… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
0
0
1
Order By: Relevance
“…The recognition of risk factors for non-preventable diseases are conducted by general doctors in the primary health care scenario, which are, in most of the places, represented by recently graduated physicians. However, studies showed that those doctors manifest a huge deficit in ophthalmology knowledge during medical school and insecurity to initially assist and/or refer ophthalmological cases, compromising the proper approach of the patients [24][25][26]. This problem is possibly correlated to the exclusion of ocular health as a mandatory subject in the Brazilian medical curriculum, and less than half have the option of undertaking an elective clerkship in ophthalmology, increasingly distancing the specialty from the reality of the general practitioner [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…The recognition of risk factors for non-preventable diseases are conducted by general doctors in the primary health care scenario, which are, in most of the places, represented by recently graduated physicians. However, studies showed that those doctors manifest a huge deficit in ophthalmology knowledge during medical school and insecurity to initially assist and/or refer ophthalmological cases, compromising the proper approach of the patients [24][25][26]. This problem is possibly correlated to the exclusion of ocular health as a mandatory subject in the Brazilian medical curriculum, and less than half have the option of undertaking an elective clerkship in ophthalmology, increasingly distancing the specialty from the reality of the general practitioner [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Em nível nacional, algumas pesquisas apontam falhas no conhecimento oftalmológico dos estudantes de medicina, o que acaba levando à insegurança durante o atendimento, quando formados. (1,5,6) Graubart et al desenvolveram instruções, endossados pela Associação Universitária de Professores em Oftalmologia (Association of University Professores in Ophthalmology -AUPO), juntamente com a American Academy of Ophthalmology, de conteúdos que possam ser utilizados nos currículos para estudantes de medicina. (7) Da mesma forma, o International Council of Ophthalmology criou um manual para alunos de medicina com assuntos que seriam os pontos-chave de aprendizado em sua formação curricular.…”
unclassified